USE OF THE DGA METHOD IN IDENTIFYING PROBLEMS ON 2 POWER TRANSFORMERS 2MVA 11.5KV- 0.4KV - Hasnira, Hasnira; Rofii' Haekal, Hadi (Journal of Electronic and Electrical Power Applications, 2023)
This study discusses the application of four Dissolved Gas Analysis (DGA) methods in identifying failure indicators in power transformers. Transformer failures can occur in the form of thermal and electrical failures, producing hazardous gases known as fault gases. The insulating oil used in power transformers plays a role in cooling and dissolving these dangerous gases to prevent unrestricted circulation. Determining the type and concentration of gases dissolved in the oil can provide information about transformer failure indicators. Therefore, DGA analysis is conducted to determine effective methods for identifying these failure signs. Oil samples were taken from transformers and analyzed using four different DGA methods. The DGA analysis results revealed varying levels of gas concentration. Based on the analysis results using the Key Gas Method, Roger's Ratio Method, Doernenburg's Ratio Method, and Duval's Triangle Method, it was found that the transformers experienced thermal damage. The Duval's Triangle Method analysis concluded that two transformers had overheated. Thus, the Duval's Triangle Method analysis can be considered an effective method for identifying disturbances in power transformers due to its simple yet effective calculations